A Comparative Study on Phenotypic versus ITS-Based Molecular Identification of Dermatophytes Isolated in Dakar, Senegal - Khadim Diongue; Ludivine Bréchard; Mamadou Alpha Diallo; Mame Cheikh Seck; Mouhamadou Ndiaye; Aida Sadikh Badiane; Stéphane Ranque; Daouda Ndiaye (International Journal of Microbiology)
Classically, dermatophytes are identified by phenotypic methods even if these methods, sometimes, remain difficult or uncertain. On the other hand, nucleotide sequence analysis of internal transcribed spacers (ITS) of rDNA has proved to be a useful method for identification of dermatophytes. The objective of this study was to compare the phenotypic method with DNA sequencing of the ITS regions for identification of dermatophyte species isolated in Dakar, Senegal. A collection of thirty-two strains of dermatophytes were isolated from patients suffering from dermatophytosis. Mycological identification revealed Trichophyton soudanense (n = 13), T. interdigitale (n = 10), Microsporum audouinii (n = 5), and one strain for each of the following species: T. rubrum, T. mentagrophytes, and M. canis and one unidentified strain. For comparison, ITS-based PCR and DNA sequencing were applied for identification of the isolated dermatophytes. ITS sequences showed, in BLAST search analysis, 99-100% of similarity. Identification of dermatophyte isolates by conventional methods was confirmed by DNA sequencing of the ITS regions in 84% of cases. Discrepancies concern mostly T. rubrum misidentified as T. interdigitale. PCR sequencing provided an excellent tool for identifying dermatophyte strains that do not present typical morphological characteristics. It was also able to give correct identification of an atypical strain of M. audouinii responsible of mycetoma of the scalp.